Heterotypic Cellular Interactions in the Ovarian Tumor Microenvironment: Biological Significance and Therapeutic Implications - Naora, Honami (Frontiers in Oncology, 2014)
The majority of women who are diagnosed with epithelial ovarian cancer present with extensive peritoneal carcinomatosis and are rarely cured by conventional chemotherapy. Ovarian cancer cells typically disseminate by shedding into the peritoneal fluid and implant on the mesothelium-lined peritoneal surfaces that overlie connective and white adipose tissues. Emerging evidence indicates that ovarian tumor progression is orchestrated by dynamic interplay between tumor cells and a variety of stromal cells such as adipocytes, endothelial cells, fibroblasts, mesenchymal stem cells, macrophages and other immune cells. This mini-review discusses the biological significance of the heterotypic cellular interactions in the ovarian tumor microenvironment and the therapeutic implications of targeting these interactions.